Problem Solving Based Assessment - ., Suyono; Priyatni, Endah Tri; Harsiati, Titik; Basuki, Imam Agus (KnE Social Sciences, 2017)
College graduates are required to have the ability to solve problems creatively in order to face the global market of this decade. To evaluate the problem-solving skills of the graduates, there is a need to develop problem solving based assessment. This study aims to produce a problem solving based assessment to test the competence of the Department of Indonesian language and literature education graduates. The design of the study is research and development using the Delphi method; the steps of which are: (1) establishing a team of panelists from a collaborative team to share the graduates standard assessment blueprint (2) discussing the assessment blueprint in terms forms and types (3) formulating the findings, (4) developing the product in the form of assessment packages, and (5) validating the product. The results of experts validation claim that this research has produced a problem solving based assessment to test the competence of the Department of Indonesian language and literature education graduates. The test has various forms and is suitable to measure high level competence. Due to the wide and deep coverage of the materials, the assessment is appropriate to measure the general competence of pre-service teacher candidates. Keywords: test, competence test, graduates, problem solving